A Critical Analysis on the Book The Fundamental Transformation of Greek Philosophy in Dealing with the Way of Islamic Thought - Abbas Ali Mansouri (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
One of the important issues in the field of Islamic philosophy is the relation between this philosophy and Greek philosophy. The main focus of the book's discussions is to study this issue. This article is intended to introduce and critique this book. In this regard, we first tried to clarify the content of the book and the main claim of the author. Finally, in the critique, we first briefly reviewed the strengths and attributes of the book and the critique of the book's form, then we entered in more detail about the book's analytical critique. The most important critique of the book is the inadequacy of the evidence and the lack of attention to the rival's arguments. According to the subject matter of the book and its scholarly methodology, it is suggested that higher education institutions consider this book as a text of educational assistance in the PhD degree in Islamic philosophy and comparative philosophy.